2015
DOI: 10.1161/circresaha.117.305262
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombospondin-1 (TSP1) Contributes to the Development of Vascular Inflammation by Regulating Monocytic Cell Motility in Mouse Models of Abdominal Aortic Aneurysm

Abstract: Rationale Histological examination of abdominal aortic aneurysm (AAA) tissues demonstrates extracellular matrix (ECM) destruction and infiltration of inflammatory cells. Previous work with mouse models of AAA has shown that anti-inflammatory strategies can effectively attenuate aneurysm formation. Thrombospondin-1 (TSP1) is a matricellular protein involved in the maintenance of vascular structure and homeostasis through the regulation of biological functions such as cell proliferation, apoptosis, and adhesion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 76 publications
10
83
2
Order By: Relevance
“…Further investigations using mice doubly deficient in both ApoE and IL-10 (64) may offer an opportunity to interrogate more closely this relationship. Although our evidence supports an important role for the proposed pathway, we recognize that it is likely that other targets for NO also play a role, such as the repression of thrombospondin-1 (65).…”
Section: (B) the Same Pattern Was Observed In Erythrocytes (G And H)mentioning
confidence: 49%
“…Further investigations using mice doubly deficient in both ApoE and IL-10 (64) may offer an opportunity to interrogate more closely this relationship. Although our evidence supports an important role for the proposed pathway, we recognize that it is likely that other targets for NO also play a role, such as the repression of thrombospondin-1 (65).…”
Section: (B) the Same Pattern Was Observed In Erythrocytes (G And H)mentioning
confidence: 49%
“…However, its underlying molecular and cellular mechanisms remain incompletely understood. Experimental evidence published by several investigative groups, including our own, suggests active interplays between infiltrating macrophages and resident SMCs (Curci and Thompson, 2004;Liu et al, 2015). Vascular SMCs are a major source of extracellular matrix proteins that render elastic property and tensile strength to the aortic wall.…”
Section: Discussionmentioning
confidence: 96%
“…Male C57BL/6J mice, aged 8-12 weeks, underwent AAA induction by elastase perfusion, as described previously (Pyo et al, 2000;Liu et al, 2015;Wang et al, 2015). In brief, after anesthesia, the abdominal aorta was isolated, and the external diameter of the largest portion of the abdominal aorta was measured with a digital caliber.…”
Section: Methodsmentioning
confidence: 99%
“…However, TSP-1 is a multifunctional protein and serves a significant role in inflammation. It has been demonstrated that TSP-1 contributes to the development of vascular inflammation by regulating the cell motility of monocytes in a mouse model of abdominal aortic aneurysm (23). Furthermore, TSP-1 efficiently down-regulates TF-induced coagulation by binding to TFPI and locating to surfaces within the extravascular space following vascular injury (32).…”
Section: Discussionmentioning
confidence: 99%
“…As a type of tumor necrosis factor-α-induced protein-8, TIPE2 is primarily expressed by the myeloid and lymphoid immune cells, particularly by T lymphocytes, mononuclear cells and macrophages (17,18). TIPE2 is a negative regulator of inflammation in certain diseases including chronic hepatitis B (19), chronic hepatitis C (20), systemic lupus erythematosus (SLE) (21), diabetic nephropathy (22) and abdominal aortic aneurysm (23), suggesting that it serves an important role in the pathogenesis of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%